Disentangling binaries and the rise of Lamanite studies. Issue 11 (29th October 2018) - Garrett, Matthew
Abstract: The rise of Lamanite studies is a peculiar phenomenon that parallels the decline of the term's usage by the church that forged the very notion. Though created for a people who initially rejected the term in the nineteenth century, many mid‐ and late‐twentieth century converts embraced the Lamanite identity. Just as the ranks of self‐identified Lamanites swelled, the Church of Jesus Christ of Latter‐day Saints' focus spilled over into international prospects, and over the past few decades, it turned away from the once special focus on those people. Nevertheless, the momentum of tens of thousands of indigenous and Latino converts necessitated a controversial discussion and analysis of such people over the past two decades. Recent scholarship increasingly invokes theoretical frameworks to better understand the process by which the Lamanite trope emerged and how it functioned among a living people.